Development and optimization of carvedilol orodispersible tablets: enhancement of pharmacokinetic parameters in rabbits - Aljimaee YH; El-Helw AM; Ahmed OA; El-Say KM (Dove Medical Press, 2015)
Yazeed HM Aljimaee,1 Abdel-Rahim M El-Helw,1 Osama AA Ahmed,1,2 Khalid M El-Say1,3 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Minia University, Minia, 3Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Al-Azhar University, Cairo, Egypt Background: Carvedilol (CVD) is used for the treatment of essential hypertension, heart failure, and systolic dysfunction after myocardial infarction. Due to its lower aqueous solubility and extensive first-pass metabolism, the absolute bioavailability of CVD does not exceed 30%. To overcome these drawbacks, the objective of this work was to improve the solubility and onset of action of CVD through complexation with hydroxypropyl-β-cyclodextrin and formulation of the prepared complex as orodispersible tablets (ODTs).Methods: Compatibility among CVD and all tablet excipients using differential scanning calorimetry and Fourier transform infrared spectroscopy, complexation of CVD with different polymers, and determination of the solubility of CVD in the prepared complexes were first determined. A Box-Behnken design (BBD) was used to study the effect of tablet formulation variables on the characteristics of the prepared tablets and to optimize preparation conditions. According to BBD design, 15 formulations of CVD-ODTs were prepared by direct compression and then evaluated for their quality attributes. The relative pharmacokinetic parameters of the optimized CVD-ODTs were compared with those of the marketed CVD tablet. A single dose, equivalent to 2.5 mg/kg CVD, was administered orally to New Zealand white rabbits using a double-blind, randomized, crossover design. Results: The solubility of CVD was improved from 7.32 to 22.92 mg/mL after complexation with hydroxypropyl-β-cyclodextrin at a molar ratio of 1:2 (CVD to cyclodextrin). The formulated CVD-ODTs showed satisfactory results concerning tablet hardness (5.35 kg/cm2), disintegration time (18 seconds), and maximum amount of CVD released (99.72%). The pharmacokinetic data for the optimized CVD-ODT showed a significant (P<0.05) increase in maximum plasma concentration from 363.667 to 496.4 ng/mL, and a shortening of the time taken to reach maximum plasma concentration to 2 hours in comparison with the marketed tablet. Conclusion: The optimized CVD-ODTs showed improved oral absorption of CVD and a subsequent acceleration of clinical effect, which is favored for hypertensive and cardiac patients. Keywords: bioavailability, Box-Behnken design, hydroxypropyl-β-cyclodextrin, oral absorption